Pre-scaling up of Improved Tef Variety in Chora District of Buno Bedele Zone Southwestern Oromia, Ethiopia - Ahmed, Nuru Temam; Hamera, Suleiman Aman; Regasa, Diriba Hordofa (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Pre-scaling up of improved Dursi variety was carried out in Chora district of Buno Bedele zone Southwestern Ethiopia with the objectives to popularize improved Dursi tef variety, to create wider demand towards improved Dursi tef variety and strength stakeholders’ linkage in the study area. The variety was scaled up on ten farmers’ fields those predominantly selected in collaboration with respective three kebeles’ Development Agents based on farmers’ willingness to provide the required land size. The land size of 25 m x 25 m was used where all the recommended agronomic practice like seed rate, fertilizer rate and weed control method were used for the accomplishment of the activity. Training was provided to Dursi growers, development agents and woreda agricultural experts to facilitate further production and dissemination of the variety. Data like number of participants on the training and yield data were recorded and analyzed using simple descriptive statistics. The result revealed that, about 124 (104 male and 20 female) participants were participated on the training. The mean grain yield of 1790 kg ha-1 was obtained which is greater than yield obtained during demonstration trial. Therefore, Dursi variety was recommended for further dissemination across numerous tef producers in the study area and similar agro ecologies.